Radical–Radical Reactions in Molecular Weight Growth: The Phenyl + Propargyl Reaction - Selby, Talitha M.; Goulay, Fabien; Soorkia, Satchin; Ray, Amelia; Jasper, Ahren W.; Klippenstein, Stephen J.; Morozov, Alexander N.; Mebel, Alexander M.; Savee, John D.; Taatjes, Craig A.; Osborn, David L. (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2023)
The mechanism for hydrocarbon ring growth in sooting environments is still the subject of considerable debate. The reaction of phenyl radical (C6H5) with propargyl radical (H2CCCH) provides an important prototype for radical–radical ring-growth pathways. We studied this reaction experimentally over the temperature range of 300–1000 K and pressure range of 4–10 Torr using time-resolved multiplexed photoionization mass spectrometry. We detect both the C9H8 and C9H7 + H product channels and report experimental isomer-resolved product branching fractions for the C9H8 product. We compare these experiments to theoretical kinetics predictions from a recently published study augmented by new calculations. These ab initio transition state theory-based master equation calculations employ high-quality potential energy surfaces, conventional transition state theory for the tight transition states, and direct CASPT2-based variable reaction coordinate transition state theory (VRC-TST) for the barrierless channels. At 300 K only the direct adducts from radical–radical addition are observed, with good agreement between experimental and theoretical branching fractions, supporting the VRC-TST calculations of the barrierless entrance channel. As the temperature is increased to 1000 K we observe two additional isomers, including indene, a two-ring polycyclic aromatic hydrocarbon, and a small amount of bimolecular products C9H7 + H. Our calculated branching fractions for the phenyl + propargyl reaction predict significantly less indene than observed experimentally. We present further calculations and experimental evidence that the most likely cause of this discrepancy is the contribution of H atom reactions, both H + indenyl (C9H7) recombination to indene and H-assisted isomerization that converts less stable C9H8 isomers into indene. Especially at low pressures typical of laboratory investigations, H-atom-assisted isomerization needs to be considered. Regardless, the experimental observation of indene demonstrates that the title reaction leads, either directly or indirectly, to the formation of the second ring in polycyclic aromatic hydrocarbons.